Strenghthening Women’s Opportunities in the Labour Market – the Case of Poland - Flaszyńska, Ewa Karolina (Olsztyn Economic Journal, 2020)
Poland is one of the countries which has made the most progress in making the labour market more available and friendly for women. The concept of supporting women is a collection of interconnected devices that create a system which is specific for Poland and which, despite functioning well in Poland, would not necessarily work well in other countries. The policy of equalisation of opportunities for women in the labour market involves many entities – not only state institutions and the state as such, but also local authorities, social partners and non-governmental organisations. Money spent on realising this policy is never regarded as wasted. The article is a review. The article presents examples of Polish solutions, which on one hand facilitate women’s inclusion into the labour market, and on the other hand, reduce unfavourable factors which constitute barriers to access to employment. It is not only support in the field of professional activation, but also a number of legal and systemic solutions. These are mainly activities aimed at creating favourable conditions for reconciling work and family life, such as the availability of childcare points, government programs, introducing paternity leave, or encouraging women to acquire qualifications.